AN EMBEDDED BASED SYSTEM FOR EMISSION LEVEL DETECTION AND RASH DRIVING PREVENTION IN VEHICLES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now a day’s air pollution caused by vehicles is rising very fast. To deal with this major problem many countries & regions have already presented a progression of emission standards. In mean time some methods has been developed, includes update ofmotor engine or get better quality of the gasoline. These actions have not enough to bring about a prominent effect as expected. Along with air pollution one more major problem is rash driving. Now a day’s rash driving is common feature of accidents. Rashdriving is a nature of driver which causes panic in the traffic & finally leads to accidents. These are critical things to control. In this paper, an automated control system along with notification system is designed with the help of this system it will be easy to overcome vehicular emission & rash driving problems. In this system semiconductor sensors are used, which gives the emissionvalues & ethanol level in driver’s breath. The microcontroller compares sensor values with predefined threshold values. If the sensors values are beyond threshold values, microcontroller triggers a buzzer & timer circuitry which indicate driver aboutthe current situation. The driver have to solve current problem in pre-defined time interval if it not the timer run out and fuel supply to engine get cutoff due to this vehicle comes to stop. Simultaneously microcontroller triggers the GSM & GPS modules to send a notification massage along with vehicle current location in the latitude and longitude values to the owner of vehicle.